Sosialisasi Identifikasi Anak Berpotensi Retardasi Mental untuk Mahasiswa Calon Guru di Kota Malang - Siti Fatimah; Annisa Fira Faradhila; Farah Dhiba Noer; Rhada Kristianasyah Putri; Muhamad Izhar Syafawi; Sri Weni Utari (Educational Consultant & Counseling Career (EC3) Mataram, 2026)
Inclusive education requires classroom teachers to accommodate children with mental retardation. However, prospective teachers' lack of competence often causes delayed interventions. This community service aimed to improve students' early identification knowledge and practical skills. Conducted in October 2014 at Universitas Negeri Malang, the program involved 120 participants. The methods included theoretical presentations, case studies, and early screening instrument simulations. The results showed a significant increase in understanding, indicated by the average pre-test score rising from 48.5 to 84.2 in the post-test. Students now possess comprehensive clinical-pedagogical skills to foster better inclusive education ecosystems in Malang City.